Global stability of a Caputo fractional SIRS model with general incidence rate - Ammi, Moulay Rchid Sidi (2021)
We introduce a fractional order SIRS model with non-linear incidence rate. Existence of a unique positive solution to the model is proved. Stability analysis of the disease free equilibrium and positive fixed points are investigated. Finally, a numerical example is presented.